Educating healthcare providers to increase Human Papillomavirus (HPV) vaccination rates: A Qualitative Systematic Review. (10th December 2019) - Leung, Shuk On Annie; Akinwunmi, Babatunde; Elias, Kevin M.; Feldman, Sarah
Abstract: Objectives: HPV vaccination rates in the United States lag behind other developed countries. Educational interventions are primarily directed at patients and parents rather than healthcare providers (HCPs), despite evidence that provider recommendation is a key determinant of vaccine uptake. The objectives for this review are to synthesize the available evidence related to the knowledge, attitudes, and beliefs of HCPs surrounding HPV vaccination, to summarize provider-specific educational interventions which have been evaluated, and to review existing provider-specific educational resources from national organizations and whether they align with the gaps identified. Methods: A systematic search was performed using PubMed, Web of Science, CINAHL, and ERIC with MeSH terms human papillomavirus, vaccine, education, workshop, training, knowledge, attitude, belief, intention, and healthcare provider. Full text articles were obtained for studies that described the knowledge and attitudes of providers and/or impact of educational interventions. Data extraction was performed by four independent reviewers. Websites of American organizations with an interest in HPV vaccination were manually searched for provider resources. Results: 1066 publications were identified, and 98 articles were fully reviewed with 40 ultimately included. Providers' knowledge on HPV was generally low with a correspondingly low vaccine recommendation rate. Provider-specific education (e.g., didactic session and communication training) with complimentary interventions demonstrated increased knowledge and vaccine series initiation and completion. Themes identified in descriptive studies highlighted providers' lack of general HPV and vaccine knowledge, low self-confidence in counselling and addressing parental concerns, and discomfort in discussing sexual issues related to vaccination. Many American organizations have provider-specific resources; however, the effectiveness of these materials has not been established. Conclusions: HPV knowledge among providers remains low. Educational interventions to improve knowledge and communication appear to be effective. A breadth of resources from national organizations are available but their efficacy and level of utilization is largely unknown. Coordinated efforts are needed to evaluate provider-specific educational resources to improve vaccine uptake in the US.